(untitled) (AI Tech International Journal, ISSN: 3079-4749, 2023)
When it comes to the development of mobile apps, the use of artificial intelligence (AI) and machine learning (ML) may offer a potential transition away from the usage of manual coding and towards a technique that is dynamic and motivated by data. The purpose of this article is to investigate the revolutionary potential that may be realised by incorporating artificial intelligence (AI) and machine learning (ML) into the process of developing mobile applications. The conventional way of manual coding is being replaced by a data-driven strategy, which gives developers the ability to build individualised user experiences, improve performance, and continuously improve mobile applications while doing so.